SMARCA4-deficient Sinonasal Carcinoma - Agaimy, Abbas; Weichert, Wilko (Head and Neck Pathology, 2017)
The term "sinonasal undifferentiated carcinoma (SNUC)" has been coined in 1986 for a highly aggressive sinonasal tract epithelial neoplasm showing distinctive morphology, but lacking any specific line of differentiation. Recent developments resulted in a dynamic splitting of new entities traditionally included in the spectrum of SNUC. Sinonasal NUT-midline carcinoma, adamantinoma-like Ewing family tumors and most recently, SMARCB1(INI1)-deficient sinonasal carcinoma are the main entities defined by specific genetic aberrations. To our knowledge, involvement of subunits of the SWItch/Sucrose Non-fermentable (SWI/SNF) chromatin remodeling complex other than SMARCB1 has not been implicated in the pathogenesis of SNUC-like neoplasms. We herein describe a 40-year-old woman who presented with a large infiltrative mass involving the right nasal cavity and the sinuses with extension into the skull base and periorbital tissue (cT4N2M0). Biopsies were interpreted initially as poorly differentiated neuroendocrine carcinoma followed by surgical resection and radiochemotherapy. No other extra-nasal tumor was detected on imaging. The patient was alive with disease at last follow-up (9 months from initial diagnosis). Histological evaluation showed poorly differentiated small round blue cell neoplasm with diffuse expression of pancytokeratin but not high molecular weight cytokeratin subsets, CK7, p63, S100, desmin or NUT. Neuroendocrine markers showed limited focal weak reactivity. SMARCB1, SMARCA2 and ARID1A were intact in the tumor cells but SMARCA4 was completely lost. This case highlights the rare occurrence of SMARCA4-deficiency in poorly differentiated sinonasal carcinomas and points to the importance of including other SWI/SNF complex subunits in the evaluation of SMARCB1-intact sinonasal malignancies.
EVALuna2:6928